The Performance of Root Morphophysiological of Some Crossing Maize (F1) on Two Medium in Rhizotron - Desy Mutiara Sari; Khairunnisa Lubis; Rosmayati Rosmayati (Jurnal Agroekoteknologi, 2017)
The objective of the research was to determine the performance of root morphophysiological of some crossing maize (F1) in acid soil using the rhizotron. The research was conducted at the green house of Faculty of Agriculture, North Sumatera University, Medan from April 2016 to June 2016. The randomized block design was used with two factors; the first factor were the crossing maizes (F1) P1 (CLA 106 x NEI 9008), P2 (NEI 9008 x CLA 106), P3 (1042-71 x CLA 84),                     P4 (CLA 84 x 1042-71), and P5 (CLA 46 x NEI 9008) and the second factor were the acid soil medium (pH 4,7 and Al-cc 0,20 me/100g) and optimum soil. The result of this research showed that the using of different soil medium significantly affected the root fresh weight, root distribution diameter, root volume, shoot fresh weight, shoot dry weight, and plant height. The using of different crossing maize (F1) showed significant effect to plant height. Interaction of both treatments had significant effect to root distribution diameter. NEI 9008 x CLA 106 performed the best growth in the acid soil whereas the CLA 84 x 1042-71 performed the best growth in the optimum soil. Keywords : acid soil, morpho-physiological appearance, rhizotron.